Therapeutic efficacy of nimodipine and topiramate on migraine and vestibular migraine; A prospective multicenter open-label study - Seo-Young Choi; Sun-Young Oh; Hyun Ah Kim; Ji‑Yun Park; Jae-Hwan Choi; Eun Hye Oh; Jeong-Yoon Choi; Seong-Hae Jeong; Seung-Han Lee; Jae-Myung Kim; Sang-Ho Kim; Hyo-Jung Kim; et al. (PLoS ONE, 2026)
Background Although new preventive treatments for migraine have emerged, it remains essential to validate the efficacy of established drugs to ensure broader therapeutic options for migraine and, in particular, for vestibular migraine where clinical evidence is more limited. This study aimed to assess the therapeutic effectiveness of nimodipine, an L-type calcium channel blocker, in patients with migraine and vestibular migraine, with reference to outcomes observed with topiramate. Methods Using a prospective open-label study involving nine referral-based university hospitals in South Korea, we recruited 850 patients (81% women, mean age ± SD = 41 ± 12) with migraine, including 255 with vestibular migraine. The primary outcome was the change in headache days over three months. The secondary outcomes included changes in pain rating scale, Migraine Disability Assessment Scale (MIDAS) and Headache Impact Test-6 (HIT-6). The outcomes of vestibular migraine included dizziness days and intensity, Dizziness Handicap Inventory, and UCLA-Dizziness Questionnaire. Results Of the 850 patients, 465 (55%) completed three months of evaluation (205 in the nimodipine group, 160 in the topiramate group, and 100 in the combination group). All groups showed a significant reduction in the headache days (1.2–2 days/week, p < 0.001) without inter-group differences ( p = 0.865). The topiramate group showed greater improvements in MIDAS and HIT-6 scores than the nimodipine ( p = 0.004) and combination groups ( p = 0.040). For vestibular migraine (n = 131), all groups improved in headache and dizziness outcomes ( p < 0.001) without inter-group differences. Adverse events leading to study discontinuation were observed only in 14 (2%) patients without a difference among the groups. Conclusion Nimodipine was associated with improvements in headache-related outcomes in migraine and in both headache- and dizziness-related outcomes in vestibular migraine. Given the observed improvements and favorable tolerability, nimodipine may be a valuable treatment option for migraine and vestibular migrain. Trial registration cris.nih.go.kr (KCT0010555).